Teori Perkembangan Kognitif Jean Piaget dan Penerapannya dalam Pembelajaran: Jean Piaget’s Theory of Cognitive Development and Its Application in Learning - Babullah, Rubi (Perkumpulan Peneliti dan Pegiat Literasi, 2022)
The background of this article is the need to understand human cognitive development according to Jean Piaget, focusing on the basic concepts and stages of development. The purpose of this study is to explore and apply Piaget's cognitive development theory in the context of learning. The research method used is a literature review, where various sources are analyzed to gain a deeper understanding of the topic. This study employs a descriptive research design to identify the challenges faced by teachers in recognizing and adjusting teaching approaches to the cognitive uniqueness of each student. The research findings highlight the importance of applying learning models that align with Piaget's theory to enhance the effectiveness of the learning process. This article proposes several learning models that can be integrated into educational practice, offering practical insights for educators in supporting students' cognitive development. The implications of this research are to assist educators and curriculum developers in implementing more effective and appropriate approaches based on cognitive development theory in the learning process. Keywords: Cognitive Development, Jean Piaget, Learning, Developmental Theory, Literature Review Abstrak: Latar belakang artikel ini adalah kebutuhan untuk memahami perkembangan kognitif manusia menurut Jean Piaget, dengan fokus pada konsep dasar dan tahapan perkembangan. Tujuan penulisan adalah untuk mengeksplorasi dan mengaplikasikan teori perkembangan kognitif Piaget dalam konteks pembelajaran. Metode penelitian yang digunakan adalah tinjauan pustaka (literature review), di mana berbagai sumber dianalisis untuk mendapatkan pemahaman yang lebih mendalam tentang topik tersebut. Penelitian ini menggunakan desain penelitian deskriptif untuk mengidentifikasi tantangan yang dihadapi guru dalam mengenali dan menyesuaikan pendekatan pembelajaran dengan keunikan kognitif setiap siswa. Temuan penelitian menunjukkan pentingnya penerapan model pembelajaran yang sesuai dengan teori Piaget untuk meningkatkan efektivitas proses belajar. Artikel ini mengusulkan beberapa model pembelajaran yang dapat diintegrasikan ke dalam praktik pendidikan, menawarkan wawasan praktis bagi para pendidik dalam mendukung perkembangan kognitif siswa. Implikasi dari penelitian ini adalah untuk membantu pendidik dan pengembang kurikulum mengimplementasikan pendekatan yang lebih efektif dan sesuai dengan teori perkembangan kognitif dalam proses pembelajaran. Kata Kunci: Perkembangan Kognitif, Jean Piaget, Pembelajaran, Teori Perkembangan, Tinjauan Pustaka